2012
DOI: 10.1016/j.geoforum.2011.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Party politics, civil society and local democracy – Reflections from Johannesburg

Abstract: Party politics is generally absent from urban governance or urban politics theories or debates, or present only anecdotally or as a 'black box', whilst they are more and more described, especially in Cities of the South, as central to urban societies, access to resources and social dynamics. This paper attempts, through the case of the role of the ANC in civil society in Johannesburg, to uncover some of the place of political parties in urban governance. It first argues that the party local branch is often cru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(33 citation statements)
references
References 36 publications
(27 reference statements)
0
31
0
2
Order By: Relevance
“…There are, however, also opportunities across and between these three areas of emphasis that have yet to be explored very much in African political geography research. We as yet know too little about how the new scramble for Africa can reconfigure urban political ecology, let alone its impacts on electoral geographies, and there has been only a thin body of work examining the implications of electoral politics for urban governance within geography, only touching on the environment or ecology via urban service delivery (Bénit‐Gbaffou ).…”
Section: Resultsmentioning
confidence: 99%
“…There are, however, also opportunities across and between these three areas of emphasis that have yet to be explored very much in African political geography research. We as yet know too little about how the new scramble for Africa can reconfigure urban political ecology, let alone its impacts on electoral geographies, and there has been only a thin body of work examining the implications of electoral politics for urban governance within geography, only touching on the environment or ecology via urban service delivery (Bénit‐Gbaffou ).…”
Section: Resultsmentioning
confidence: 99%
“…In Cape Town, the level of participation in Mitchell Plains CPF is much higher than a few years ago (Fourchard, 2011); in some popular neighbourhoods in eThekwini (Meth, 2011) and in Johannesburg (Dube et al, 2010;Bénit-Gbaffou, 2012), CPFs have become new objects of local power competition. The rise of participatory mechanisms at the local level through ward committees on the one hand, and the increase in political competition (internal or external to the ANC) on the other, still make community policing a rich field for power competition and community initiatives experimentation.…”
Section: Community Policing -Shifts In the Model And Unexpected Effectsmentioning
confidence: 97%
“…Brogden and Nijhar (2005) take the view that CPFs have been largely a failed experiment, and they argue that there is little remaining support for this model of community policing outside of wealthy former-white areas. On another level, there is growing evidence to suggest that CPFs are in fact far from moribund in low-income neighbourhoods, even if they have not been entirely effective in providing security (Fourchard, 2009;Meth, 2011;Bénit-Gbaffou, 2012): CPFs remain a key political object at the local level, and are involved in local leadership battles between political parties and local leaders. From the police's perspective, Marks et al (2009) contend that the narrative of community policing remains an important tool for the South African Police Services (SAPS), reflected in their policy documents and in their basic training programs.…”
Section: Community Policing In South Africa and The Neoliberal Debatementioning
confidence: 99%
“…Similarly, in states characterised by clientelism, it is often suggested that individuals lack the financial autonomy required to make decisions that would oppose the wishes of their patrons or the parties the patrons represent (Chatterjee, 2011). Since the electoral victory of the African National Congress in 1994, the relationship between partisan loyalty, democracy and patronage has fed intense debates in South Africa (Bénit-Gbaffou, 2012;Piper and Ancioni, 2015). Without employment prospects other than through patronage, it is feared that citizens will not exercise their responsibilities to be critical, advocate for decisions in the public interest, and hold the state to account.…”
Section: Pedagogies Of Citizenshipmentioning
confidence: 99%